Classification Techniques In Blood Donors Sector – A Survey - Che Khalid, Nor Syuhada; Mohd Aboobaider, Burhanuddin; Ahmad, Asmala; Abd Ghani, Mohd Khanapi (Universiti Teknikal Malaysia Melaka, 2013)
This paper focuses on the classification and the recent trends associated with it. It presents a survey of the classification system and clarifies how classification and data mining are related both to each other. Classification is arranging the blood donor dataset into the predefined group and helpful to predict group membership for data instances. This enables users to search target donors become easier because the blood stocks always required replacing expired stocks after a certain period and useful in emergency demands such as surgery and blood transfusion. This paper has also sought to identify the research area in classification to fulfill gaps where further work can be carried on.